Update in Systemic and Targeted Therapies in Gastrointestinal Oncology - Nelson S. Yee (Biomedicines, 2018)
Progress has been made in the treatment of gastrointestinal cancers through advances in systemic therapies, surgical interventions, and radiation therapy. At the Multi-Disciplinary Patient Care in Gastrointestinal Oncology conference, the faculty members of the Penn State Health Milton S. Hershey Medical Center presented a variety of topics that focused on this sub-specialty. This conference paper highlights the new development in systemic treatment of various malignant diseases in the digestive system. Results of the recent clinical trials that investigated the clinical efficacy of pegylated hyaluronidase, napabucasin, and L-asparaginase in pancreatic carcinoma are presented. The use of peri-operative chemotherapy comprised of 5-fluorouracil or capecitabine, leucovorin, oxaliplatin, and docetaxel (FLOT), and immunotherapy including pembrolizumab, nivolumab, and ipilimumab in gastroesophageal carcinoma are discussed. Data from clinical trials that investigated the targeted therapeutics including nivolumab, ramucirumab, lenvatinib, and BLU-554 are reported. The role of adjuvant capecitabine in resected biliary tract carcinoma (BTC) and nab-paclitaxel in combination with gemcitabine and cisplatin in advanced BTC are presented. In colorectal carcinoma, the efficacy of nivolumab, adjuvant FOLFOX or CAPOX, irinotecan/cetuximab/vemurafenib, and trifluridine/tipiracil/bevacizumab, is examined. In summary, some of the above systemic therapies have become or are expected to become new standard of care, while the others demonstrate the potential of becoming new treatment options.